Exploring New Metaphors for a Networked World through the File Biography - Lindley, Siân; Smyth, Gavin; Corish, Robert; Loukianov, Anastasia; Golembewski, Michael; Luger, Ewa; Sellen, Abigail (2018 CHI Conference on Human Factors in Computing Systems, 2018)
We present a body of work undertaken in response to the challenge outlined by Harper et al. in their paper, 'What is a File?' [9]. Through a conceptual and design-led exploration of new file metaphors, we developed the 'file biography', a digital entity that encompasses the provenance of a file and allows the user to keep track of how it propagates. We explored this through prototyping and utilised it in two user studies. In the studies, we (i) asked people to sketch out file biographies for their own content, and (ii) deployed a tool enabling users to build their own simple file biographies across multiple versions of Word documents. We conclude that new file metaphors may need to play different roles for different types of digital content, with a distinction being drawn between content that is 'in production' and virtual possessions that are, in a sense, a 'finished' artefact.